Analisis Deskriptif Faktor yang Mempengaruhi Rendahnya Minat Melanjutkan Pendidikan ke Perguruan Tinggi di SMKN 9 Padang - Feby Rahmawati; Linda Fitria; Popi Radyuli (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
This research, titled "Descriptive Analysis of Factors Affecting Low Interest in Continuing Higher Education at SMKN 9 Padang," aims to identify and analyze the factors influencing the low interest of Grade XII students at SMKN 9 Padang in continuing their education to higher institutions during the 2024/2025 academic year. This study adopts a descriptive quantitative approach, using random sampling techniques to collect data from 204 respondents. The data were gathered through questionnaires, which were validated, resulting in a total of 38 items to measure interest in continuing education and 19 items to measure the factors influencing low interest. Descriptive statistical analysis reveals that the factors affecting low interest have a mean value of 58 with a standard deviation of 7, while the interest in continuing education to higher institutions has a mean value of 56 with a standard deviation of 10. The normality test with a significance value of 0.493 > 0.05 indicates that the data are normally distributed. The linearity test also indicates a linear relationship between the independent and dependent variables with a significance value of 0.936 > 0.05. Hypothesis testing using Pearson Product-Moment Correlation reveals a significant correlation between the factors influencing low interest and the interest in continuing education to higher institutions, with a correlation coefficient of 0.628 and a significance level of < 0.001. The study concludes that factors such as economic conditions, social support, academic readiness, and perceptions of higher education significantly impact the low interest of SMKN 9 Padang students in pursuing further education. These findings are crucial for school authorities and policymakers to design interventions that can enhance students' interest in continuing their education at higher institutions.